Pawning N00bs: Insights into Perceptions of Brand Extensions of the Video Game Industry. Issue 3 (August 2017) - Butcher, Luke; Tang, Ysobel; Phau, Ian
This paper examines gamers' perceptions of video game brand extensions through a grounded-theory qualitative methodology. Results of the focus groups and interviews reveal deep and highly contextual information pertaining to gamer characteristics (discernment and fanaticism) and extension characteristics (affordability, collectability, fit, identity-projection, and ownership), as well as the moderating roles of marketing effectiveness, interpersonal influences, and inelasticity of demand on gaming brand equity. Results provide substantial academic value and deeper insights into this culturally and economically significant industry, with distinct implications for product design, consumer segmentation, and promotion.